Phylogeny of the weevil genus Rhinusa Stephens based on adult morphological characters and host plant information (Coleoptera: Curculionidae) - Caldara, Roberto; Sassi, Davide; Toševski, Ivo (Zootaxa, 2010)
A phylogenetic analysis of the species belonging to the weevil genus Rhinusa Stephens, 1829 (Coleoptera: Curculionidae: Curculioninae: Mecinini) was carried out. Rhinusa weevils feed on plants of the closely related families Scrophulariaceae and Plantaginaceae. Based on a cladistic analysis of six outgroup and 33 ingroup taxa, and 39 adult morphological and 8 ecological characters, eight well supported species groups and two monobasic groups belonging to three separate and more inclusive assemblages were recognized. The first assemblage (A) includes nine species belonging to two groups (R. bipustulata and R. tetra groups), whereas the second and third assemblages (B and C) include a total of 14 species belonging to two groups (R. antirrhini and R. linariae groups) and six groups (R. pilosa, R. herbarum, R. neta, R. vestita, R. mauritii and R. melas groups), respectively. Two of the three main assemblages (A and B) are well supported as monophyletic entities, whereas the third assemblage (C) has weak support contingent in part upon the exclusion of host plant associations. Assemblage A includes all species living on species of Scrophulariaceae, with two groups occurring on two closely related plant genera, Scrophularia (R. bipustulata group) and Verbascum (R. tetra group), respectively. The other two assemblages include species living exclusively on species of the family Plantaginaceae, tribe Antirrhineae. These patterns suggest a well conserved and phylogenetically congruent association among the weevils and their hosts. Optimizing host plant preferences onto the morphological phylogeny indicates that feeding on Plantaginaceae was the plesiomorphic condition for the genus Rhinusa. In general there are no strict relationships between groups of weevils and their specific feeding habits; however, species of the R. antirrhini group are all feeding on seed capsules. In contrast, in other groups the larvae of closely related species display significant variations in host plant parasitism. Some species of the R. tetra group feed on seed capsules whereas others are stem borers. In turn, certain species of the R. neta group feed on seed capsules yet others are inquilines of gall forming species of Rhinusa. The latter habit is present in multiple convergent groups such as the R. linariae and R. pilosa groups.